Self-Care Behaviors and Associated Factors Among Hypertensive Patients at Dessie Referral Hospital, Northeast Ethiopia - Assen Muhe; Mesfin Haile Kahissay; Mohammed K. Ali; Solveig A. Cunningham; Bruck Messele Habte (International Journal of Hypertension)
Conclusion: Adherence to self-care among hypertensive patients is alarmingly low, influenced by diagnosis duration, residency, and BMI. Addressing hindrances like living conditions, work, cultural norms, and peer influence is vital. Healthcare providers must focus on education that promotes behavior change and support. Patient engagement in self-care is essential. Future research should investigate healthcare organizational and provider influences. Implementing these strategies could markedly improve hypertension management and patient outcomes.